Wild Burmese python nest site selection, thermogenesis, and brooding behaviors in the Greater Everglades Ecosystem - Andrea F. Currylow; Lisa M. McBride; Gretchen E. Anderson; Jacquelyn C. Guzy; Matthew F. McCollister; Christina M. Romagosa; Kristen M. Hart; Amy A. Yackel Adams (Ecosphere)
Abstract Invasive Burmese pythons (Python bivittatus) are extremely cryptic animals. Although their conservation status in their native range is Vulnerable, in the Greater Everglades Ecosystem (Florida, USA) they have become a dominant destructive force and usually are immediately removed whenever found. This poses a paradox where removals are occurring, yet the study and understanding of python ecology is needed to inform removal methods. An important component of life history includes the nesting season, but little is known about python nest site selection, nest brooding, thermogenesis, or hatching success in the wild. Here, we present the first complete and most detailed report of oviposition and brooding for this biologically significant time period of a female Burmese python. We describe anthropogenic nest site selection, document the extent of shivering thermogenesis, describe brooding behaviors, and provide photo‐documentation of complete hatching of the largest python clutch on record.